2016
DOI: 10.1016/j.psychres.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum levels of bioavailable vitamin D and negative symptoms in first-episode psychosis

Abstract: Total vitamin D levels had been commonly reported to be lowered in patients with chronic psychotic illnesses in countries from the higher latitudes. However, studies on patients with first episode psychosis (FEP) are limited. In this study we investigated serum concentrations of total and bioavailable vitamin D levels in FEP patients compared to healthy controls and the association between symptom severity and vitamin D components. A total of 31 FEP patients and 31 healthy controls were recruited from Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
17
4
Order By: Relevance
“…We identified that 80% (n=134) had suboptimal vitamin D levels (<20ng/L) at first contact for psychosis, a much higher proportion than the previously reported 50% (n=10) with vitamin D levels <30ng/ml at FEP (Graham et al, 2015). We identified a mean vitamin D level of 13.8ng/ml (n=168) at study recruitment, much lower than the previously identified mean vitamin D levels in FEP of 28.2 ng/ml (n=20) (Graham et al, 2015), 61.7 ng/ml (n=31) (Yee et al, 2016) and 44.8 ng/ml (n=71) (Nerhus et al, 2015). This finding may be a reflection of the ethnicity distribution of our sample.…”
Section: Prevalence Of Vitamin D Insufficiency/deficiencycontrasting
confidence: 72%
See 2 more Smart Citations
“…We identified that 80% (n=134) had suboptimal vitamin D levels (<20ng/L) at first contact for psychosis, a much higher proportion than the previously reported 50% (n=10) with vitamin D levels <30ng/ml at FEP (Graham et al, 2015). We identified a mean vitamin D level of 13.8ng/ml (n=168) at study recruitment, much lower than the previously identified mean vitamin D levels in FEP of 28.2 ng/ml (n=20) (Graham et al, 2015), 61.7 ng/ml (n=31) (Yee et al, 2016) and 44.8 ng/ml (n=71) (Nerhus et al, 2015). This finding may be a reflection of the ethnicity distribution of our sample.…”
Section: Prevalence Of Vitamin D Insufficiency/deficiencycontrasting
confidence: 72%
“…The lack of an association between vitamin D levels (both categorical and continuous) and negative symptoms of psychosis at baseline, but the identified association with negative symptoms at 12 months, raise the possibility that low vitamin D at onset of psychosis may be associated with the later emergence of negative symptoms. Like previous work in FEP, we failed to identify a cross sectional relationship between vitamin D levels and positive (Graham et al, 2015;Nerhus et al, 2015;Yee et al, 2016) or negative symptoms (Nerhus et al, 2015).…”
Section: Vitamin D and Clinical Symptomscontrasting
confidence: 45%
See 1 more Smart Citation
“…Some studies concluded that significantly lower vitamin D concentrations and higher vitamin D deficiency rate were observed in the schizophrenic group compared with the matched control group, 8,28,29 which were consistent with our conclusions. However, others reported statistically undifferentiated vitamin D concentrations in the schizophrenic group, such as the case-control studies from Yee et al, 9 Graham et al, 30 and Norelli et al 31 All the contributions showing no significant correlation adopted routine immunologic methods to determine vitamin D concentrations, which could lead to inaccurate results due to the inevitable presence of cross reaction and incomplete extraction of 25(OH)D from vitamin D-binding protein. 32 LC-MS/MS has been considered the reference method of vitamin D quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a rapidly increasing number of observational studies exhibited the essential neuroprotective effects of these vitamins. For instance, vitamin D has presented a wide spectrum of neurobased functions, such as influencing neurotransmitter expression and neuroplasticity development, [8][9][10] as well as facilitating neuronal differentiation and maturation. 11 In consideration of the research findings that oxidative stress was believed to contribute to schizophrenia pathophysiology, 12,13 the well-known antioxidant vitamins (vitamins A and E) were likely to play important protective roles in schizophrenia by preventing oxidative damage.…”
mentioning
confidence: 99%